Repetitive transcranial magnetic stimulation (rTMS) for schizophrenia patients treated with clozapine. (2nd January 2021) - Wagner, Elias; Honer, William G.; Sommer, Iris E.; Koops, Sanne; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Dlabac-De Lange, Jozarni J.; Bais, Leonie; Knegtering, Henderikus; Aleman, André; Novak, Tomas; Klirova, Monika; et al.
Abstract: Objectives: Biological strategies to improve treatment efficacy in clozapine-treated patients are urgently needed. Repetitive transcranial magnetic stimulation (rTMS) merits consideration as intervention for patients with persistent auditory hallucinations (AH) or negative symptoms (NS) not responding sufficiently to clozapine treatment. Methods: Data from 10 international RCTs of rTMS for patients being treated with clozapine were pooled. Two levels of symptomatic response were defined: improvement of ≥ 20% and ≥ 50% on study-specific primary endpoint scales. Changes in the positive and negative syndrome scale (PANSS) from baseline to endpoint assessment were also analysed. Results: Analyses of 131 patients did not reveal a significant difference for ≥ 20% and ≥ 50% response thresholds for improvement of AH, negative or total symptoms between active and sham rTMS groups. The number needed to treat (NNT) for an improvement in persistent AH was nine following active rTMS. PANSS scores did not improve significantly from baseline to endpoint between active and sham groups in studies investigating NS and AH. Conclusions: rTMS as a treatment for persistent symptoms in clozapine-treated patients did not show a beneficial effect of active compared to sham treatment. For AH, the size of the NNTs indicates a possible beneficial effect of rTMS.